Critical analysis and digital documentation of the transformations of heritage buildings - İrem Bekar; Izzettin Kutlu (Vitruvio: International Journal of Architectural Technology and Sustainability)
Trabzon Hagia Sophia Mosque symbolizes significant cultural heritage with its historical diversity and distinctive architectural features. Today, this building is remarkable for its cultural transformation and historical layers. The study aims to address the transformation processes of the Hagia Sophia Mosque in the light of international conservation criteria, to understand the history of the building and to reveal the digital perspectives of this historical place. The study comprises a four-stage process: (1) investigating the building’s history through a literature review, (2) obtaining visual and technical data through fieldwork, (3) conducting a transformation analysis and generating a three-dimensional measured model, and (4) providing evaluations and recommendations on the building’s transformation and digital modeling in alignment with conservation criteria. The digital model of the building as a result of the study will be part of the preservation of such an important piece of cultural heritage for future generations. The study emphasizes the need for more effective integration of digital modeling techniques in conservation and documentation studies, extending from Hagia Sophia to various cultural heritage sites.